2021
DOI: 10.1038/s41467-021-26367-9
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular delivery of protein drugs with an autonomously lysing bacterial system reduces tumor growth and metastases

Abstract: Critical cancer pathways often cannot be targeted because of limited efficiency crossing cell membranes. Here we report the development of a Salmonella-based intracellular delivery system to address this challenge. We engineer genetic circuits that (1) activate the regulator flhDC to drive invasion and (2) induce lysis to release proteins into tumor cells. Released protein drugs diffuse from Salmonella containing vacuoles into the cellular cytoplasm where they interact with their therapeutic targets. Control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 65 publications
0
92
0
1
Order By: Relevance
“…The results indicated that the good anchoring ability and penetration properties of microrobots (Figure d). It should be noted that bacteria invasion to cells is closely associated with flagella, which sense the cell surface and determine the optimal location for invasion. We then tested the ROS level in CT26 cells cocultured with the microrobots under the AMF. Figure e showed that the EcN@MNP + MH group significantly elevated the intracellular ROS level as compared to the MNP + MH group.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the good anchoring ability and penetration properties of microrobots (Figure d). It should be noted that bacteria invasion to cells is closely associated with flagella, which sense the cell surface and determine the optimal location for invasion. We then tested the ROS level in CT26 cells cocultured with the microrobots under the AMF. Figure e showed that the EcN@MNP + MH group significantly elevated the intracellular ROS level as compared to the MNP + MH group.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, protein drug delivery to tumors was demonstrated by Raman et al The group used intracellular delivery of Salmonella to express constitutive two-chain active caspase-3, an engineered form of caspase-3 that causes apoptotic cell death. They developed the strain by engineering genetic circuits to enable autonomous deposition of protein payloads directly into cancer cells that decreased tumor growth and reduced breast metastases [ 48 ]. Transforming growth factor alpha (TGFα) is a natural ligand for epidermal growth factor receptor (EGFR), a receptor highly expressed in tumor cells [ 49 ].…”
Section: Why Is Salmonella the Best Option?mentioning
confidence: 99%
“…The drug-carrying microcells showed significant inhibition on the growth of breast cancer without any significant toxicity. Raman et al (2021) developed a Salmonella vector with controlled drug synthesis and cellular invasion and achieved effectively reduced tumor growth and metastasis. Salmonella -based protein delivery shows a safe and effective treatment for tumors to provide new therapy for untreatable cancers.…”
Section: Bacteria-mediated Antitumor Therapymentioning
confidence: 99%